Analisis perkembangan likuiditas bank bca syariah berdasarkan current ratio periode 2020-2024 - choirina, rizqin mufidah; Aisyah, Esy Nur (Maliki Interdisciplinary Journal, 2025)
Liquidity is an important indicator in assessing a bank’s ability to meet short-term obligations without disrupting its operational stability. The Current Ratio (CR) is one of the ratios widely used in analyzing liquidity because it illustrates the comparison between current assets and short-term liabilities. This study aims to analyze the development of Bank BCA Syariah’s liquidity during the 2020–2024 period based on the Current Ratio. The research method uses a descriptive quantitative approach by utilizing secondary data obtained from Bank BCA Syariah’s annual financial reports. The results of the study are expected to provide an overview of the bank’s liquidity stability over the past five years, as well as identify patterns of change that can serve as a reference for bank management, investors, and other stakeholders in decision making. This study is also expected to contribute to the literature on liquidity management in Islamic banking in Indonesia.